1.8-0.4x=0.5x-2.7化简
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 07:50:39
1.8-0.4x=0.5x-2.7化简1.8-0.4x=0.5x-2.7化简1.8-0.4x=0.5x-2.7化简1.8-0.4x=0.5x-2.71.8+2.7=0.9X4.5=0.9XX=5
1.8-0.4x=0.5x-2.7化简
1.8-0.4x=0.5x-2.7化简
1.8-0.4x=0.5x-2.7化简
1.8-0.4x=0.5x-2.7
1.8+2.7=0.9X
4.5=0.9X
X=5
1.8-0.4x=0.5x-2.7化简
8x-5.5x=7.57.2x÷3.6=2 3x+6x-8x=0.7 12x-2x-5x=4.512x-x=0 5x+x=1.8 3.2x+1.8x=64.8x-0.8x=6 6.3-0.3x=9.6 8.6x-8.5x=0.720x-2x=36 9x+6x=4.5 18x-12x=5.42x-1.6x=3.6 18x+3x=7×6 1.2x-0.5x=0.71.3x+2.7x=1 4x-3.2x=6.4 0.8x+3.2x+3x=562.8x-2x=7.2
0.5x(x+4)-0.4(x+4)=3.2
解方程 x-25-(x-25)*0.4=0.5x
x/0.5-0.4x-0.6/0.2=2(-x+3)
1.8(0.5x-2)=0.5x
7.72-x=1.8(x+0.4)
0.4x-0.6=0.2x-1.8
0.4x-0.6=0.2x-1.8
1.8-0.4x=0.2x-0.6
0.5(x+0.4)=x-1.
0.3x+0.65=0.4x+0.5
(2000*0.4)+x /(2000+x )=0.5
0.5x+0.4(15-x)=7
240-X=0.4(0.5X)
0.4(x+9)=0.5(10.8-x)
化简1+x+x(1+x)+x(1+x)²;+L+x(1+x)2012=
化简1+x+x(1+x)+x(1+x)²;+L+x(1+x)2012=